(untitled) (Multidisciplinary Journal of Science and Technology, 2025)
The development of mathematical ideas in preschool children plays a crucial role in shaping their cognitive abilities and logical thinking skills. Early childhood is a sensitive period for forming basic concepts such as number, size, shape, and spatial relationships. However, several issues hinder this process, including insufficient methodological support, lack of individualized approaches, and limited integration of play-based learning strategies. This paper explores the challenges faced by educators in fostering mathematical understanding at the preschool level and highlights the importance of combining didactic methods with interactive, game-based activities. Emphasis is placed on the role of teachers, family involvement, and modern educational technologies in addressing these issues and ensuring effective mathematical development in early childhood.